Supply Chain Performance Measurement Practices of Indian Industries - Joseph Durai Selvam; Georgy Kurien; M. N. Qureshi (International Journal of Supply Chain Management, 2020)
In any Industry the Supply chain performance plays a crucial role and it is vital in growth of the industry. Through this study an attempt is made to find some insight to the supply chain performance measurement practices of Indian industries through an exploratory survey. The study reveals almost all the respondents (84%) felt that supply chain performance measurement system employed in their organisation has a clear purpose. Also the study reveals that most supply chain performance measurement system provides high importance to quality measurements and includes both financial and non-financial indicators. The study gave clarity in understanding the objectives of implementing supply chain performance measurement systems and metrics (measures) used in supply chain performance measurement systems The Multivariate analysis revealed three factors emerged from this study are ‘Strategic Orientation’ followed by ‘Internal Focus’ and ‘Motivation and Control’.